PSYCHOLOGICAL TRAINING IN FOOTBALL (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Questions of differential sports psychology are considered. The general and specific indices of sportsmen's adaptation were revealed. The psychological characteristics of football players that influence the success of psychological adaptation to the conditions of competitive activity are revealed.